2023
DOI: 10.1021/acs.langmuir.2c03114
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Containing Triblock Copolymer Vesicles with Microphase-Separated Structure

Abstract: Introduction of a fluorine-containing block into block copolymers is an effective method to tune block copolymer nanoassemblies with a microphase-separated structure. However, this microphase-separated structure is difficult to clearly observe due to its nanoscale size. In this work, fluorine-containing ABC triblock copolymer vesicles of poly(ethylene glycol)-block-polystyrene-block-poly(4-vinylbenzyl pentafluorophenyl ether) (PEG-b-PS-b-PVBFP) are synthesized by reversible addition–fragmentation chain transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Bai et al reported dual-responsive physicalcompartmentalized polymersomes by the coassembly of βcyclodextrin-acylhydrazone-doxorubicin (β-CD-hydrazone-DOX) and azobenzene-terminated poly(2-(dimethylamino)ethyl methacrylate) (Azo-PDMA-FA) for ultraviolet light and pH triggered three-stage programmed drug release. 110 First, DOX was released from physically compartmentalized polymersomes slowly. Next, ultraviolet light promoted the dissociation of β-CD/Azo, leading to the shape transformation and quick release of DOX.…”
Section: Programmed Delivery and Biological Applications Of Mcpsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bai et al reported dual-responsive physicalcompartmentalized polymersomes by the coassembly of βcyclodextrin-acylhydrazone-doxorubicin (β-CD-hydrazone-DOX) and azobenzene-terminated poly(2-(dimethylamino)ethyl methacrylate) (Azo-PDMA-FA) for ultraviolet light and pH triggered three-stage programmed drug release. 110 First, DOX was released from physically compartmentalized polymersomes slowly. Next, ultraviolet light promoted the dissociation of β-CD/Azo, leading to the shape transformation and quick release of DOX.…”
Section: Programmed Delivery and Biological Applications Of Mcpsmentioning
confidence: 99%
“…More importantly, this polymer could be integrated into the phospholipid membrane, which acted as a synthetic molecular channel and improved the permeability of the molecule. Very recently, Zhang and co-workers reported phase-separated vesicles self-assembled from a fluorine-containing triblock copolymer PEG- b -PS- b -PVBFP. As shown in Figure A,B,D, the synthesized PEG 45 - b -PS 197 - b -PVBFP 233 polymersomes were relatively large size of about 216 nm, and their membrane thickness was about 28 nm.…”
Section: Structural Features Of Mcpsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address these issues, the PISA method was developed. It can directly prepare diblock copolymer nanoparticles with controllable morphology [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , and high concentration (50 wt%), offering the advantages of simplicity, efficiency, and repeatability. With the advancement of PISA, initiation is no longer limited to thermal methods, leading to the emergence of greener and more energy-efficient initiation mechanisms and supportive methods.…”
Section: Introductionmentioning
confidence: 99%